The effects of participatory processes on public policy development in Kenya’s devolved governments - Kenyatta, Gloria Nyambura (2024)
Abstract: This dissertation examines the effects of the participatory processes on public policy development in Kenya’s devolved governments. Although public participation during policymaking in Kenya is a constitutional requirement, the procedures for its implementation are not prescribed by the law. Therefore, this dissertation focuses on participatory processes (informal) whose implementation procedures are not foreseen by the law, and their results are unbinding. The central objective is to explore the performance and effectiveness of these processes during public policy development, especially to establish if they are undertaken for superficial legitimacy or to enhance the policymaking process, as the Constitution of Kenya 2010 envisions. The research compares two devolved governments in Kenya, Nairobi City (urban) and Lamu (rural), to establish the commonalities and differences in the participatory processes during their execution. The research uses the “most different” design for its comparative analysis and the framework for Comparison of Participatory Processes (COPP) to assess the context, process, and outcome levels of these processes. The study employs qualitative data collection techniques supplemented with mixed surveys. The research reveals that the administrators in both counties have substantial leeway to determine the processes to use. They have opted for low-cost participatory processes due to the inadequate funds allocated to public participation. However, these processes are not the most effective and legitimacy-generating participatory mechanisms. Further, participatory processes are conducted by non-practitioners who are not well-prepared to undertake them effectively. Civic education is also not conducted in both counties to create awareness of these processes, their importance and to train the public on how to participate. The research further discloses that although both counties have established some institutional frameworks, they have not yet achieved a satisfactory level of institutionalization that can impact public participation. In addition, the research exposes that the execution of these processes does not adjust to most local contextual factors as the administrations focus more on one contextual element of financial resource capacities, overshadowing others that can promote quality participation if considered. While in the eyes of the majority of the study’s target groups, participatory processes have contributed to fulfilling some of their expectations in policymaking, the neglect of local contexts and the lack of political will by the policymakers to sustain these processes are significant setbacks that have contributed to their poor implementation, and thus unsatisfactory results. Furthermore, despite both counties being in different settings, they exhibit major similarities in executing participatory processes due to the usage of low-cost participatory processes, which are designed and implemented similarly. Therefore, based on the findings, considering appropriate process-level yardsticks linked to contextual factors is essential for quality participation and better policy outcomes. Overall, the study recommends three overarching perspectives that the local public administrations should rethink to address the unsustainability, power asymmetries, and ineffectiveness of these processes: political will (sustainability element), power redistribution (equality element), and location-specific contexts (quality element)